To Predict Mortality of Critically Ill Neonates Admitted in Intensive Care Unit (ICU) of a Tertiary Care Pediatric Hospital (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Critically ill neonates who need intensive care are vulnerable to various derangement. Early and prompt recognition of these predictor helpful to care and their correction improves survival of these neonates.Objective: To predict mortality of critically ill neonates admitted in ICU.Methods: This observational study was carried out at NICU of Dhaka Shishu (Children) Hospital from January 2015 to July 2015. Total 121 neonates were enrolled according to inclusion criteria and analyzed their valuable biochemical profile specially electrolyte and blood gas status as a part of proper management as well as to predict their outcome.Results: Among critically sick neonates, perinatal asphyxia was common disorder followed by sepsis. Biochemical profile specially electrolyte and acid-base disruption play important role to the outcome of critically sick neonates. Low pH, low potassium and high base-deficit level were found to have significant consequence.Conclusion: Perinatal asphyxia constitute major cause of admission of critically sick neonates. Early detection of electrolyte and acid-base status is helpful to care and overall survival of these neonates. Mortality was the highest among neonatal sepsis followed by perinatal asphyxia. Metabolic acidosis and hypokalaemia were the predict or of outcome of these such neonates.DS (Child) H J 2018; 34(1) : 15-21